Manual educativo online acessível sobre hipertensão arterial: avaliação da aprendizagem de cegos e videntes - Carvalho, Luciana Vieira (2018)
Hypertension has high prevalence and low control among the population. Due to the peculiarities inherent to their disability, blind people become more exposed to the risk factors of the disease, demonstrating their need to be included in accessible educational strategies. The aim of this study was to validate an accessible online educational manual on arterial hypertension for the learning of the blind and seeing people. It consists in a multi-method study with methodological and quasi-experimental research. Data collect took place from January 2017 to March 2018, at the Health Communication Laboratory of the Nursing Department of the Federal University of Ceará and at educational institutions for the blind in Fortaleza, Ceará. For the validation of the manual took part health professionals as specialists, blind and seeing people. The manual was constructed according to five stages of the Model of Design and Development of Digital Educational Material called Analysis and Planning; Modeling; Implementation; Evaluation and Maintenance and, Distribution. In the Analysis and Planning stage, an action plan was elaborated to define the structure of the manual. In the Modeling stage, content was selected on hypertension and health promotion measures. Experts validated both the content through the Educational Content Validation Tool and the affirmatives of pre and post-test instruments. 16 frames of storyboards were created to add texts and media, which were later transformed into 16 pages in Hypertext Markup Language format divided into six didactic modules. Accessibility features such as text boxes, return and advance buttons, and audio description were created. In the Implementation stage, accessibility tests were performed with screen readers. Two errors were found, and inconsistencies were corrected. A pilot test was performed with 10 subjects who considered the manual accessible. Evaluation and Maintenance occurred during all phases of the model. In the Distribution stage, the manual was hosted on a private server for evaluation of the learning by the target population. 117 people attended, in which 72 seeing and 45 blind. There was a predominance of non-hypertensive individuals (81.2%); women (63.2%); 18-39 years (43.6%); secondary education (47.9%); Catholic (72.6%); employed (53.8%); receiving income up to 2 minimum wages (61.5%). Regarding the evaluation of learning, when comparing the correct affirmatives between pre- and post-test, a significant increase (p <0.0001) in the post-test average scores was observed at all levels of complexity, with a higher proportion in high complexity ones. In the analysis of learning by variables, in all groups compared (Deficiency, Hypertension, Gender, Age, Schooling, Marital Status, Religion, Occupation and Income) there was an increase in the average of correct affirmatives in the post-test. In the assessment of quality with the Assistive Technology Assessment Questionnaire, it was observed that all items of the attributes Objectives, Access, Clarity, Structure and Presentation, Relevance and Efficiency, and Interactivity with minimum agreement of 80% by the majority of participants were adequate. Items that received the highest percentage of positive responses were related to the learning stimulus; search for information without difficulties; content needed for understanding; organized; arouses interest; interaction and easy navigation. It has been concluded that the manual is valid and reliable for the learning of both blind and seeing people, contributing to health promotion on hypertension, and can be used by nurses and other health professionals to empower the population.